Sinantropia de los Calliphoridae (Diptera) de Valdívia, Chile - FIGUEROA-ROA,LUIZ (2002)
The objective of this study was to determine synathropic index of adult Calliphoridae (Diptera) collected in the city of Valdívia, Chile (39º48 S; 73º15 ' W). For this, samples were taken monthly between September 1996 and August 1997 in three different localities representing urban, rural and natural environments. Rat carcass, fish , and chicken viscera were used as baits. Four blowfly species were collected: Calliphora vicina Robineau-Desvoidy, the dominant species in all three baits and sites of capture, followed by Lucilia sericata (Meigen), both species being eusynanthropic. The other two species, Compsomyiops fulvicrura (Robineau-Desvoidy) and Sarconesia magellanica (Le Guillou), were collected in smaller numbers and were characterized respectively as hemysinanthropic and asynanthropic. In addition to the synanthropic index, the monthly abundance and the efficiency of the baits as attractans to the flies as well as their medical and sanitary importance were also determined and discussed.